Questions: Simplify the radical. √((-12)^2+(16)^2) √((-12)^2+(16)^2)= (Type an exact answer, using radicals as needed.)

Simplify the radical.
√((-12)^2+(16)^2)
√((-12)^2+(16)^2)=
(Type an exact answer, using radicals as needed.)
Transcript text: Simplify the radical. \[ \sqrt{(-12)^{2}+(16)^{2}} \] \[ \sqrt{(-12)^{2}+(16)^{2}}= \] (Type an exact answer, using radicals as needed.)
failed

Solution

failed
failed

Simplify the radical \(\sqrt{(-12)^{2}+(16)^{2}}\).

Calculate \((-12)^{2}\).

\((-12)^{2} = 144\).

Calculate \((16)^{2}\).

\((16)^{2} = 256\).

Add the results.

\(144 + 256 = 400\).

Take the square root of the sum.

\(\sqrt{400} = 20\).

\(\boxed{20}\)

\(\boxed{20}\)

Was this solution helpful?
failed
Unhelpful
failed
Helpful